• TITLE: Comparison of intracameral injection with subconjunctival injection of dexamethasone for postoperative inflammation in congenital cataracts - Rana, Afia Matloob; Raza, Ali; Akhter, Waseem (Pakistan Journal of Ophthalmology, 2021)
ABSTRACT: Introduction: Cataract affects a huge population around the globe and equally affects Pakistani population. Children with congenital cataract presents with huge deformity and dependence, the consequences are lifelong if not treated with better management at right time. In this study we aimed at comparing intracameral and subcojunctival injection of dexamethasone in congenital cataract in terms of postoperative inflammation. Purpose: The purpose of our study is comparing the role of intracameral injection with subconjunctival injection of dexamethasone in preventing immediate postoperative inflammation after congenital cataract extraction and to make the ground for better option for programmatic implementation in these cases. Study Design: Randomized control trial Place and duration of study: Holy Family Hospital, Rawalpindi since june 2014 to May 2015. Material and methods: In this RCT, 190 children with congenital cataract were enrolled in the department of ophthalmology, Holy Family Hospital, Rawalpindi. Patients were selected using a random table, 95 cases each in intracameral injection and subconjunctival injection of dexamethasone groups.The study duration was one year from june 2014 to May 2015. Ethical approval was granted by hospital ethics committee and patients were administered a written informed consent at enrolment. The outcome measure was intraocular inflammation after surgery for extraction of cataract. Results: Male cases were in majority in group B (58.9%) whereas in group A females (55.8%) were in majority. Mean age was6.43 ± 4.69 years in Group-A compared to 5.85 ± 4.10 years in Group-B. Frequency of posterior synechiae (inflammation) was 4.21% (n=4) in Group-A (intracameral) compared to 15.79% (n=15) in Group-B (subconjunctival) which was significantly different (p-value, 0.007). Conclusion: Intracameral injection is better than subjunctival injection of dexamethasone in the management of post-operative inflammation in children with congenital cataract.